Character Education Based on Religious Values: an Islamic Perspective - Ismail Ismail (Ta'dib: Jurnal Pendidikan Islam, 2016)
Character education in Indonesia has become a necessity that can not be negotiable. Various cases of crime and moral deviations become evident that the character of most citizens already at alarming stage. Therefore, since the beginning, national education is not only aimed at generating human intelligent and skilled, but also of noble character. This is realized through the introduction of 18 characters excel in school (religious, honest, disciplined, tolerance, and so on). In the Islamic perspective character education paired with akhlak (Islamic ethics) education. Among the important characteristics are: it sourced from the Quran Hadith; Prophet Muhammad as a role model; priority-based methods of mental-spiritual (soul management, habituation, exemplary, and healthy environment); are simultaneous in which three education centers, namely schools, families, and communities should play a role in synergy. The government and the mass media also play a role in supporting the education of character. Pendidikan karakter di Indonesia telah menjadi kebutuhan yang tidak dapat ditawar. Berbagai kasus kejahatan moral dan penyimpangan menjadi jelas bahwa karakter sebagian besar warga sudah pada tahap mengkhawatirkan. Oleh karena itu, sejak awal, pendidikan nasional tidak hanya bertujuan menghasilkan manusia cerdas dan terampil, tetapi juga karakter yang mulia. Hal ini diwujudkan melalui pengenalan 18 karakter berprestasi di sekolah (agama, jujur, disiplin, tolerann, dan sebagainya). Dalam pendidikan karakter perspektif Islam dipasangkan dengan pendidikan akhlak (etika Islam). Di antara karakteristik penting adalah: itu bersumber dari al-Quran Hadis; Nabi Muhammad sebagai panutan; metode berbasis prioritas mental-spiritual (manajemen jiwa, pembiasaan, keteladanan, dan lingkungan yang sehat); yang simultan di mana tiga pusat pendidikan, yaitu sekolah, keluarga, dan masyarakat harus berperan dalam sinergi. Pemerintah dan media massa juga berperan dalam mendukung pendidikan karakter.